Resistencia civil no armada en Medellín. La voz y la fuga de las comunidades urbanas (2009)
ABSTRACT: This article intends to show that civil population under the control of armed actors is not always a passive victim of violence and the armed aggression, neither that its attitude is inevitably of submissive loyalty in the presence of such control. It is showed how, in urban contexts signed by the control and violence of armed actors, like what occurs in the city of Medellin, poor neighborhood communities – particularly neighborhood communes 8, 9 and 13- have gone through multiple and varied experiences of non armed civil resistance to the war and violence. The article tries to show that the social, political, economic and cultural scenario and dynamics of urban territories, have not only been played the armed actors but also by the neighborhood communities who, through their leaderships and collective actions, many times performed underground, oppose resistance to armed control.